PENGARUH JARAK TANAM TERHADAP POPULASI DAN PERSENTASE SERANGAN Thrips parvispinus KARNY (THYSANOPTERA: THRIPIDAE) PADA TANAMAN CABAI BESAR (Capsicum annuum L.) DI KINTAMANI, KABUPATEN BANGLI, BALI - I Wayan Dirgayana; Dicky Marsadi; Made Mika Astuthi (MEDIAGRO, 2022)
Thrips parvispinus is a pest of large chili plants Capsicum Annuum. This study aimed to determine the effect of spacing on the population and the percentage of T. parvispinus attacks on large chili C. annuum in Kintamani, Bangli Regency, Bali. This research has been conducting on farmer's land in Sekaan Village, Kintamani District, Bangli Regency, Bali from March to May 2021. This study used a randomized block design (RAK) method, with three treatment levels and five replications. The number of plants observed in each plot was ten plant clumps using a systematic sampling method (diagonal system). The results showed differences in the number of T. parvispinus pests on large chili plants in each treatment, there was an apparent difference between the spacing treatment one (1) and the spacing treatment two (2), but the spacing treatment two (2) was not significantly different from treatment three (3). The results showed that the percentage of T. parvispinus attack on spacing treatment one (1) was higher than treatment spacing two (2) and three (3) from observation one to observation six. The relationship between harvest yields and the percentage of T. parvispinus pest attacks showed differences in harvest weight. The spacing treatment one (1) has a smaller harvest weight than the spacing treatment two (2) and three (3). So the proper spacing for large chili C. annuum is the spacing treatment two and three.